Multi-criteria evaluation of wheel/rail degradation at railway crossings. (April 2020) - Wei, Zilong; Núñez, Alfredo; Liu, Xiubo; Dollevoet, Rolf; Li, Zili
Abstract: This study evaluates the degradation of wheels and rails at railway crossings. The evaluation method is composed of 1) finite element simulation of dynamic wheel/crossing interaction and 2) multi-criteria analysis of wheel/rail degradation in terms of yield behavior, rolling contact fatigue (RCF) and wear. With the aid of this method, we conducted a case study identifying the proper yield strength of rail steel material for a 54E1-1:9 crossing under a specified traffic condition. The case study indicates that the wear of contact bodies is more sensitive to train speed compared with yield and RCF; the increase of rail yield strength suppresses rail degradation while exacerbating wheel degradation; and rail yield strength in the range of 500–600 MPa is preferred to achieve a good trade-off between the wheel and rail degradations. Highlights: A method is proposed to evaluate the degradation of wheels and rails at railway crossings. The method uses finite element simulation and multi-criteria analysis. Wheel/rail degradation is evaluated in terms of yield behavior, rolling contact fatigue (RCF) and wear. A case study is conducted to identify the proper yield strength of rail steel material for a 54E1-1:9 crossing.